The affect heuristic in occupational safety - Savadori, Lucia; Caovilla, Jessica; Zaniboni, Sara; Fraccaroli, Franco (La Medicina del Lavoro, 2015)
Background: The affect heuristic is a rule of thumb according to which, in the process of making a judgment or decision, people use affect as a cue. If a stimulus elicits positive affect then risks associated to that stimulus are viewed as low and benefits as high; conversely, if the stimulus elicits negative affect, then risks are perceived as high and benefits as low. Objectives: The basic tenet of this study is that affect heuristic guides worker’s judgment and decision making in a risk situation. The more the worker likes her/his organization the less she/he will perceive the risks as high. Method: A sample of 115 employers and 65 employees working in small family agricultural businesses completed a questionnaire measuring perceived safety costs, psychological safety climate, affective commitment and safety compliance. Results: A multi-sample structural analysis supported the thesis that safety compliance can be explained through an affect-based heuristic reasoning, but only for employers. Conclusions: Positive affective commitment towards their family business reduced employers’ compliance with safety procedures by increasing the perceived cost of implementing them.